Properties of building materials - Eldridge, H. J. (Medical and Technical Publishing Construction, 1974)
This listing of the properties of building materials puts into effect the recommendations of the CIB that such properties should be presented in a systematic manner according to an internationally agreed standard method. The tables first appeared as one of the sections of the Construction Industry Handbook. Their usefulness gained widespread recognition and it is in response to meny requests for this material to be made available separately, in a format convenient for quick reference, that this volume has benn produced. The result is a uniquely practical volume dealing with the important materials in a clear, concise and easily understood manner.